2016
DOI: 10.1016/j.ijsu.2016.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of the neutrophil/lymphocyte ratio in diagnosing adult strangulated inguinal hernia

Abstract: Among the different clinical features, the NLR appears to be the best index in diagnosing SIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 20 publications
2
29
1
Order By: Relevance
“…NLR has also been used in the diagnosis of adult strangulated inguinal hernias. Zhou et al [ 19 ] reported that NLR>6.5 was significantly related to the presence of a strangulated inguinal hernia. These authors suggested that NLR>6.5 may serve as the best predictor for diagnosing strangulated inguinal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…NLR has also been used in the diagnosis of adult strangulated inguinal hernias. Zhou et al [ 19 ] reported that NLR>6.5 was significantly related to the presence of a strangulated inguinal hernia. These authors suggested that NLR>6.5 may serve as the best predictor for diagnosing strangulated inguinal hernias.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that ischemia-modified albumin seems to be an effective predictive marker of early detection of necrosis in patients with incarcerated hernias. In the study about the patients with strangulated inguinal hernia by Zhou et al, [11] they studied the clinical value of NLR. NLR of the patients with obvious bowel ischemia was higher than that of the patients without bowel ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 6 ] Studies have demonstrated their predictive role not only on the progress and prognosis of many internal diseases, but also infectious complications following various surgical procedures such as cesarean section, [ 7 ] rectal cancer surgery, [ 8 ] curative gastrectomy for gastric cancer [ 9 ] and hepatectomy. [ 10 ] Recent studies also generalize the application of NLR to the field of hernia surgery and it was be found to be significantly associated with persistent postsurgical pain bowel, [ 11 ] the presence of a strangulated inguinal hernia, [ 12 ] and bowel resection in incarcerated groin hernia patients. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%